Federal Legal Protections for Educators with Disabilities - Donald F. Uerling (Educational Considerations, 2007)
Educators are generally aware that federal law protects persons with disabilities from unjustified discrimination, but they may not be familiar with the details of how these protections come into play when decisions are made about an individual’s educational or employment opportunities.
Keywords: Rehabilitation Act; Federal Statutes; employment; public services; accommodations; disability